HEALTH HABITS, DIGITAL MEDIA, AND PUBLIC SCHOOL: RESULTS OF A STUDY WITH ADOLESCENTS IN ANANINDEUA, PA (BRAZIL) - Bessa, Valéria de Nazaré de Paula; Palheta, Éder do Vale; Palmeira, Biratan dos Santos; de Sousa, Moisés Simão Santa Rosa; do Couto, Cileide Tavares Borges; da Costa, Márcia de Araujo; dos Santos, Marco Antônio Barros; da Silva, Dario Deivid Silva (Seven Editora, 2026)
This study analyzed the formation of health habits during adolescence, considering their relationship with social, economic, and institutional factors, with emphasis on the role of the school as a strategic space for promoting well-being. The research was conducted through questionnaires applied to students from a public school in the municipality of Ananindeua (PA), allowing the identification of perceptions, practices, and challenges related to nutrition, physical activity, and the use of digital media. The results showed that although adolescents recognize the importance of a healthy lifestyle, they face multiple structural, financial, emotional, and cultural barriers to transforming this knowledge into daily practice. The hypotheses demonstrated that educational strategies in the school environment increase students’ awareness of health and self-care; however, such actions are still punctual and poorly integrated into the school curriculum. Practical and culturally contextualized programs favored greater student engagement, although they are limited by the lack of infrastructure and continuous public policies. In addition, excessive use of digital media was identified as a risk factor, but it can be re-signified as a pedagogical resource when critically mediated. It is concluded that the school plays a central role in building healthy habits; however, its effectiveness depends on permanent, intersectoral actions sensitive to youth realities, integrating education, health, and social participation.